2011
DOI: 10.5943/mycosphere/2/5/7
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of fungal endophytes in medicinal plants of Courtallam hills, Western Ghats, India

Abstract: A total of 3634 endophytic fungal isolates were recovered from 4800 leaf, stem and bark segments of 10 medicinal plants growing in Courtallam hills, Western Ghats, south India, during monsoon, winter and summer seasons. These isolates belonged to coelomycetes (26.35%), hyphomycetes (21.76%), Xylariaceae (0.6%) and mycelia sterilia (3.55%). Colonization frequency of endophytic fungi varied significantly between seasons. The fungal community from leaves was most diverse followed by stem and bark tissues. Alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 39 publications
3
2
0
Order By: Relevance
“…The genus Colletotrichum is isolated from all the three study sites considered for the study. This corresponds with earlier reports on colonization of endophytic fungi that suggest that the genus Colletotrichum is often isolated as dominant endophytic fungi from several medicinal plants species (29)(30)(31). In the present study, the crude metabolites of 14 out of the 18 (77.78%) fungal strains showed prominent antimicrobial activity against at least one of all the test pathogens considered.…”
Section: Discussionsupporting
confidence: 92%
“…The genus Colletotrichum is isolated from all the three study sites considered for the study. This corresponds with earlier reports on colonization of endophytic fungi that suggest that the genus Colletotrichum is often isolated as dominant endophytic fungi from several medicinal plants species (29)(30)(31). In the present study, the crude metabolites of 14 out of the 18 (77.78%) fungal strains showed prominent antimicrobial activity against at least one of all the test pathogens considered.…”
Section: Discussionsupporting
confidence: 92%
“…Tejesvi et al (2005) found that the endophytic colonization frequency was greater in inner bark (18.5%) than twigs (4.6%), in Terminalia arjuna, while the bark samples harboured more endophytes than twig samples in Crataeva magna . Similar results have been reported in many previous endophyte studies , Thalavaipandian 2011.…”
Section: Discussionsupporting
confidence: 81%
“…[25] found higher Shannon-Weaver diversity indices of endophytic fungi in twigs than in leaves of the six plants reported, likewise Simpson dominance index and Shannon diversity index showed the same result as above [27]. Other findings have supported that the leaf samples showed more diversity of endophytic fungi than the stem and bark samples [28]. Simpson"s diversity index value range between 0 and 1, where an increasing index value equates to an increase in species diversity.…”
Section: Resultssupporting
confidence: 73%